The art and science of the pitch the ultimate playbook for pitching to partners, investors, and reality TV shows - Aguilar, John (Singapore Penguin Random House SEA, 2022)
Serial entrepreneur and The Final Pitch creator and host John Aguilar shares valuable lessons, tips and techniques he picked up from years of producing and hosting the reality pitching show. In this book, he straddles the East and the West to interview world-renowned investors, venture capitalists, conglomerates, startups, creatives, and legal and financial experts to identify the components of a pitch that makes an impact-whoever you are, wherever you are, and at whatever stage of your idea, start-up, or scale-up. He dives deep into the minds and methods of founders who pitched their way to million-dollar valuations, and tackles lessons that can be learned from those who failed.
Keywords: Finance, Personal -- Juvenile literature; Investments -- Juvenile literature; Financial security -- Juvenile literature; Wealth -- Juvenile literature